A 16-Channel Cassette Recorder and Telephone Transmitter with CRT Based Display for Clinical EEG - Vives, Juan Quemada (1981)
Description of a prototype, now under clinical evaluation, able to transmit over the public telephone network, or to record on a cassette, sixteen channels of EEG signal with 40 Hz bandwidth. Received or reproduced signals are displayed on a CRT. Description of the multiplexion and modulation techniques used, and discussion of results and measures. The system is microprocessor based and uses time compression multiplexing.